Acoustic compatibilization material, preparation method thereof, loudspeaker module and electronic equipment

By loading porous materials in hosting carriers such as porous carbon materials or porous silica to form a multi-stage porous structure, the problems of existing materials in the pore distribution and crystallization state are solved, and the low-frequency effect and sound absorption performance of the speaker are significantly improved.

CN119603591APending Publication Date: 2025-03-11SSI NEW MATERIAL (ZHENJIANG) CO LTD

Patent Information

Application Number
CN202411672641.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing acoustic improvement materials cannot accurately control the distribution and direction of the pore structure during the preparation process, and the oxide materials cannot form crystalline substances, resulting in poor acoustic capacity enhancement effect.

Method used

Acoustic capacitance materials with a shelter-shaped structure are used to load or embed porous materials in perimeter carriers such as porous carbon materials or porous silica to form a multi-stage porous structure, which improves the adsorption and desorption ability of gas molecules.

Benefits of technology

Significantly improve the low frequency effect of the speaker, expand the virtual volume of the speaker, improve the sound absorption performance of the acoustic capacity-enhancing material, and the material itself has a molded appearance without the need to introduce molded adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119603591A_ABST
    Figure CN119603591A_ABST
Patent Text Reader

Abstract

The invention provides an acoustic compatibilization material, a preparation method thereof, a loudspeaker module and electronic equipment. The acoustic compatibilization material comprises a living carrier and a porous material, the living carrier has a pore structure, and the pore structure comprises mesopores and macropores; the porous material is loaded or embedded in the pore structure of the living carrier; the porous material is provided with # imgabs0 two-dimensional pore channels and / or three-dimensional pore channels, and the pore channels are communicated with one another. The invention also provides a preparation method of the acoustic compatibilization material, which comprises the following steps: immersing the living carrier in a solution of a porous material precursor, and crystallizing to obtain the acoustic compatibilization material, the preparation method does not comprise a roasting step. The invention further provides a loudspeaker module which comprises the acoustic compatibilization material. The invention further provides an electronic device. The electronic device comprises the loudspeaker module. The acoustic compatibilization material provided by the invention has a hierarchical pore structure, has a relatively good acoustic compatibilization effect, and can effectively improve the low-frequency effect of a loudspeaker.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of loudspeaker manufacturing, and in particular to an acoustic volume-increasing material and a preparation method thereof, a loudspeaker module and an electronic device. Background Art

[0002] Zeolite molecular sieve is one of the commonly used porous materials for improving speaker acoustics, but the water absorption and low-frequency improvement performance of zeolite molecular sieve materials still need to be improved.

[0003] In the prior art, acoustically active articles can be made from inorganic agglomerates, which have an average size of 50 μm-2 mm and contain a network of carbon or silicon dioxide and metal oxide particles embedded in the network, which can reduce the resonant frequency of acoustic devices in the frequency range of 50 Hz to about 1500 Hz.

[0004] There is also existing technology for preparing virtual acoustic materials through emulsion in-situ synthesis methods. This type of method usually uses organic silica gel as a silicon source and adhesive, aluminum oxide, aluminum hydroxide, fumed silica, etc. as a structural regulator, and nano-micron-level carbon black as a porogen. The organic silica and other components are dissolved or dispersed evenly by a low-boiling point solvent, and then microspheres with a particle size range of 50 microns to 2 mm are prepared by suspension polymerization in an aqueous phase system containing a surfactant. After high-temperature calcination in an aerobic environment to remove the porogen and hydrocarbon components, a white porous composite inorganic microsphere material is obtained. The microsphere product with a particle size range of 50μm-1000μm obtained in this way can greatly reduce the actual volume of the speaker without affecting its acoustic effect.

[0005] However, the above acoustic improvement materials have the following problems: In the above schemes, the raw materials for preparing the improvement materials are usually porous oxide materials such as aluminum oxide and carbon dioxide. These porous materials are formed by carbonizing organic carbon tissue in the presence or absence of oxygen to form a porous structure. The distribution of organic carbon in the carbonization process is uncontrollable, and the formation of pores is greatly affected by the distribution of organic carbon. Therefore, the above method cannot accurately control the distribution and direction of the pore structure. In addition, oxides such as aluminum oxide and silicon dioxide cannot form crystalline substances in the above preparation process, and there is a lack of regularly distributed pore structures inside these oxide structures. Summary of the invention

[0006] In order to solve the above problems, the purpose of the present invention is to provide an acoustic volume-increasing material and a preparation method thereof, a speaker module and an electronic device. The acoustic volume-increasing material has a multi-level pore structure, has a good acoustic volume-increasing effect, and can effectively improve the low-frequency effect of the speaker.

[0007] In order to achieve the above object, the present invention provides an acoustic volume-enhancing material, which includes a host carrier and a porous material, wherein the host carrier has a pore structure, the pore structure includes mesopores and macropores, and the porous material is loaded and / or embedded in the pore structure of the host carrier;

[0008] The porous material has two-dimensional pores and / or three-dimensional pores. And the channels are interconnected (that is, the two-dimensional channels can be interconnected, the three-dimensional channels can be interconnected, and the two-dimensional channels and the three-dimensional channels can also be interconnected).

[0009] The above-mentioned acoustic volume-increasing material is a parasitic structure, and the porous material is loaded and / or embedded in the pore structure of the parasitic carrier to form a parasitic structure. The parasitic structure can make the pore structure in the parasitic carrier cooperate with the pore structure in the porous material, which can improve the adsorption and desorption ability of the acoustic volume-increasing material for gas molecules, thereby significantly improving the low-frequency effect. In addition, the acoustic volume-increasing material with a parasitic structure itself has a molded appearance and a suitable size, and there is no need to introduce a molding adhesive to mold the acoustic volume-increasing material.

[0010] In the above-mentioned acoustic volume-enhancing materials, the host carrier generally has a porous structure, at least with mesopores and macropores. Among them, the mesopores can provide channels for the circulation of gas molecules, and can also be used for the adsorption and desorption of gas molecules; the macropores can be used to load or grow porous materials, and the macropores can also be used together with the mesopores to adsorb and desorb gas molecules to achieve a sound-absorbing effect, and cooperate with the porous material to achieve an acoustic volume-enhancing effect. In some specific embodiments, the pore size of the mesopores of the host carrier is 2nm-50nm, and the pore size of the macropores of the host carrier is usually 50nm-20μm.

[0011] In the above-mentioned acoustic volume-enhancing material, the host carrier may include one or a combination of two or more of porous carbon materials, porous silica, etc. Further, the porous carbon material may include one or a combination of two or more of carbonized coconut shell, soft carbon, hard carbon (such as lignite, etc.), carbon molecular sieve, functionalized activated carbon (such as alkaline-modified activated carbon), etc., and the functionalized activated carbon may include alkaline-modified activated carbon.

[0012] In the above acoustic volume-enhancing material, the host carrier can withstand a temperature above 200° C., so that the host carrier can withstand the crystallization temperature and crystallization process of porous materials such as molecular sieves, thereby preventing the structure of the host carrier from being affected by the crystallization process.

[0013] In the above-mentioned acoustic capacity-enhancing materials, the porous material can expand the virtual volume of the speaker to perform acoustic capacity-enhancing and thus improve the low-frequency effect by absorbing and desorbing air during the change of external pressure.

[0014] In the above-mentioned acoustic volume enhancement material, the porous material generally has two-dimensional channels and / or three-dimensional channels; further, the porous material may have two-dimensional microporous channels and / or three-dimensional microporous channels.

[0015] In the above acoustic volume enhancement material, the porous material has microporous channels, and the porous material has at least a pore size of The above pores (specifically, they can be two-dimensional pores or three-dimensional pores); further, the pore diameters of the pores in the porous material can be in the range of The porous material has a diameter of 2 nm or more (more preferably less than or equal to 2 nm); and the pores are interconnected and can penetrate the porous material, so that gas molecules (mainly nitrogen molecules) can freely enter and exit the pores of the porous material to achieve an acoustic volume expansion effect. The porous material may specifically include an inorganic material with micropores and / or an organic skeleton material with micropores.

[0016] In the above-mentioned acoustic volume-enhancing material, the organic framework material with micropores may include one or a combination of two or more of metal organic framework materials (MOFs), hypercrosslinked polymers (HCPs), conjugated microporous polymers (CMPs), covalent triazine frameworks (CTFs), porous aromatic frameworks (PAFs), etc. The organic framework material with micropores has regularly arranged micropore channels inside, which can be used to adsorb and desorb gas molecules in the air.

[0017] In the above-mentioned acoustic capacity-enhancing material, the inorganic material having micropores may include molecular sieves and the like.

[0018] In the above acoustic volume-enhancing material, the molecular sieve may have a higher specific surface area and a higher adsorption capacity for air. In some specific embodiments, the specific surface area of ​​the porous material may reach 250 m 2 / g or more, further reaching 350m 2 / g or above.

[0019] In the above-mentioned acoustic volume-enhancing material, the porous material used in the present invention can be a crystalline material, such as a molecular sieve, and generally has a higher degree of crystallinity. Therefore, the porous material of the present invention has a higher degree of structural order than the amorphous material and has more regularly distributed pores. In some specific embodiments, the crystallinity of the molecular sieve can reach more than 80%. The crystallinity is a relative crystallinity, which can be calculated based on the ratio of the total area of ​​the crystallization peak and the total area of ​​all the peaks (the sum of the areas of the crystallization peak and the amorphous peak), and the calculation formula is:

[0020] Crystallinity (%) = ∑A crystalline / (∑A crystalline +∑A amorphous ), where A crystallineis the area of ​​the crystallization peak, A amorphous is the area of ​​the amorphous peak.

[0021] In the above-mentioned acoustic capacity-enhancing material, the molecular sieve may include one or a combination of two or more of phosphorus aluminum molecular sieve, pure silicon molecular sieve, silicon aluminum molecular sieve, silicon phosphorus aluminum molecular sieve, etc. Among them, for silicon aluminum molecular sieve, in order to achieve structural electrical neutrality, extra-framework cations are usually introduced into the silicon aluminum molecular sieve, and the silicon aluminum molecular sieve used in the present invention may further contain one or a combination of two or more of hydrogen ions, monovalent metal ions, divalent metal ions, trivalent or higher metal ions, etc. In some specific embodiments, the molecular sieve may include ZSM-5 molecular sieve and / or Beta molecular sieve, etc.

[0022] The present invention does not impose any specific restrictions on the ratio of framework elements in the molecular sieve. Preferably, for the silicon-aluminum molecular sieve, a molecular sieve with a high silicon-aluminum ratio can be used to improve the water absorption resistance of the acoustic compatibilizer material, and further, the silicon-aluminum ratio (i.e., the silicon-aluminum molar ratio) is above 50.

[0023] According to a specific embodiment of the present invention, the mass ratio of the host carrier to the porous material can be 4:1-1:4, for example, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 and other specific values, and a range with any two of the above specific values ​​as endpoints. In some specific embodiments, the mass ratio of the host carrier to the porous material can be 2:1-1:2.

[0024] According to a specific embodiment of the present invention, the acoustic volume-increasing material can be used as a volume-increasing material in a loudspeaker. The acoustic volume-increasing material can expand the virtual volume in the loudspeaker and improve the low-frequency effect.

[0025] The present invention also provides a method for preparing the acoustic volume-increasing material, comprising immersing a host carrier in a solution of a porous material precursor and crystallizing the solution to obtain the acoustic volume-increasing material; wherein the preparation method does not include a calcination step.

[0026] In the above preparation method, the particle size of the host carrier is usually controlled to be 30-50 mesh, such as 30-40 mesh.

[0027] In the above preparation method, before immersing the porous material precursor solution, the above preparation method may include an operation of pre-treating the host carrier.

[0028] When the host carrier is carbonized coconut shell, the pretreatment process may include: subjecting the host carrier to high temperature treatment at 450°C-800°C in a protective atmosphere for more than 2 hours (such as 4 hours). The protective atmosphere may be nitrogen or the like. The pretreatment process will not have a significant effect on the distribution and orientation of the pores in the host carrier, but can reduce the amount of water adsorbed by the host carrier and fully carbonize the host carrier. The fully carbonized host carrier has a high degree of openness of the pores inside, close to full openness, and the porosity and surface area of ​​the host carrier are also improved, which is beneficial to increase the load of the host carrier on the porous material. In some specific embodiments, the above-mentioned pretreatment may further include: before the high-temperature treatment, subjecting the host carrier to a first screening, ball milling, a second screening, and drying process.

[0029] In the above preparation method, when the host carrier is porous silica, the pretreatment process of the host carrier may include: mixing a silicon source (such as silica sol, etc.) with ammonia water to obtain a gel, drying to allow water molecules and ammonia molecules to escape, crushing, first screening, ball milling, second screening, drying, and completing the pretreatment.

[0030] In the above preparation method, when the host carrier is hard carbon, the pretreatment process of the host carrier may include: drying the hard carbon (lignite, etc.) to remove moisture and volatile components, carbonizing it at high temperature in a protective atmosphere (such as nitrogen), the carbonization temperature may be 1500°C, the carbonization time may be 12 hours, crushing the carbonized product, screening it for the first time, ball milling it, screening it for the second time, drying it, and completing the pretreatment.

[0031] In the above pretreatment process, the particle size of the host carrier obtained after ball milling can reach 30-50 meshes, and the host carrier after ball milling can remove irregular edges and corners and present an ellipsoid or sphere. After the first screening, particles with a particle size of 20-40 meshes can be obtained, and after the second screening, particles with a particle size of 30-40 meshes can be obtained.

[0032] In the above preparation method, the porous material precursor solution includes a molecular sieve mother solution, such as a molecular sieve mother solution without a template.

[0033] In the above preparation method, the molecular sieve as a porous material is generally prepared by a synthesis method without a template agent, such as a seed induction method, etc. No template agent is introduced in the process of synthesizing the porous material, and the subsequent process of calcining to remove the template agent can be omitted, thereby retaining the pore structure in the porous material and the pore structure in the carrier. Therefore, the molecular sieve mother solution usually does not contain a template agent.

[0034] In the above-mentioned preparation method, the molecular sieve mother liquor can be a solution that can prepare molecular sieve by crystallization. According to the type of elements contained in the molecular sieve, the molecular sieve mother liquor can include one or more combinations of silicon source, aluminum source and phosphorus source. Further, the molecular sieve mother liquor can also generally include an alkali source, a mineralizer, etc., and the mineralizer is used to promote the dissolution of the silicon source and the aluminum source. The mineralizer can be a soluble inorganic salt, and the mineralizer can be removed in the washing process after crystallization. The ratio of each component in the molecular sieve mother liquor can adopt a conventional molecular sieve raw material ratio. For example, when the molecular sieve is a silicon-aluminum molecular sieve, the mass ratio of the aluminum source to the silicon source (in terms of SiO2) can be (1-3): 30.

[0035] In the above preparation method, the molecular sieve can be synthesized by seed induction method, and the molecular sieve mother solution can contain seed crystals. The amount of seed crystals added can be added according to the conventional molecular sieve synthesis raw material ratio, for example, the mass ratio of seed crystals to SiO2 in the silicon source can be (1-6):100, for example (3-6):100.

[0036] In the above preparation method, the crystallization conditions can be adjusted according to the type and degree of crystallization of the porous material. For example, when the porous material is a molecular sieve, the crystallization conditions can be 120°C-160°C for 36h-96h. Generally, the crystallization temperature does not exceed 200°C (i.e., the crystallization temperature is less than or equal to 200°C) to avoid changes in the pore structure of the host carrier during the crystallization process.

[0037] According to a specific embodiment of the present invention, the above preparation method may include:

[0038] Step 1, pretreatment: the parasitic carrier is screened for the first time, and then ball-milled, during which the shape of the carrier tends to be regular (such as spherical or ellipsoidal); the parasitic carrier after ball milling is screened for the second time to obtain a parasitic carrier with a particle size of 30-50 mesh, and dried (the condition can be dried at 60° C. for 12 hours); the parasitic carrier after drying is subjected to a high temperature treatment at 450-800° C. for more than 2 hours (for example, 4 hours) to obtain a pretreated parasitic carrier;

[0039] Step 2: immerse the pretreated host carrier in the solution of the porous material precursor, stir to make the solution fully wet the host carrier, and crystallize (when the porous material is a molecular sieve, the crystallization conditions can be 120° C.-160° C. for 36 h-96 h) to obtain the acoustic volume-enhancing material. In step 2 of the above preparation process, high-temperature treatment such as calcination is not performed.

[0040] The present invention also provides a speaker module, which includes the above-mentioned acoustic volume-increasing material. In some specific embodiments, the acoustic volume-increasing material can be filled, sprayed or coated at any position of the speaker module to achieve multiple functions such as sound absorption and shock absorption.

[0041] According to a specific embodiment of the present invention, the acoustic volume-increasing material can be filled inside the speaker module. More specifically, a speaker can be provided in the resonance cavity of the speaker module, and the acoustic volume-increasing material is filled in the resonance cavity of the speaker module. By filling the acoustic volume-increasing material in the inner cavity of the speaker module, the adsorption and desorption capacity of air can be improved, the virtual volume of the speaker can be expanded, and the effect of improving low frequency can be achieved.

[0042] The appearance of the acoustic volume-enhancing material provided by the present invention can be adjusted according to actual needs (such as the shape of the cavity filled by the material), and can be granular, block, sheet, etc. For example, the appearance of the acoustic volume-enhancing material can be changed by bonding and other means to present a granular, block, sheet, etc. shape.

[0043] The present invention also provides an electronic device, which includes the above-mentioned speaker module. In some specific embodiments, the electronic device can be a smart phone, a smart watch, a tablet computer, smart glasses, VR glasses, a smart speaker or a laptop computer (especially a thin and light laptop computer), etc.

[0044] According to a specific embodiment of the present invention, the electronic device is provided with a sound output opening and a sound output channel, and the speaker module is acoustically coupled with the sound output opening through the sound output channel.

[0045] According to a specific implementation of the present invention, the speaker module is integrally formed with the electronic device; or, the electronic device further includes a casing, and the speaker module is disposed in an internal space formed by the casing.

[0046] The beneficial effects of the present invention include:

[0047] The acoustic volume-increasing material provided by the present invention combines the advantages of light weight and large air adsorption of the carrier material, and the advantages of regular pores and pore structures of porous materials such as molecular sieve materials, by loading porous materials such as molecular sieves in a porous structure. The acoustic volume-increasing material has a multi-level pore structure, which is conducive to air adsorption and desorption, can significantly expand the virtual volume of devices such as speakers, has an acoustic volume-increasing effect and improves low-frequency performance, and can replace existing zeolite materials as sound-absorbing materials. In addition, the acoustic volume-increasing material provided by the present invention is itself a molding material, and does not need to be molded with the aid of an adhesive, which improves the product's resistance to VOCs (volatile organic compounds) and has the characteristics of environmental protection and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Schematic diagram of the preparation process of the acoustic capacity-enhancing materials of Examples 3 to 6.

[0049] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution curve of the molecular sieve of comparative example 1 are shown.

[0050] Figure 3 This is the SEM picture of the carbonized coconut shell in Preparation Example 1.

[0051] Figure 4 , Figure 5 This is a SEM photograph of the acoustic capacity-enhancing material prepared in Example 2.

[0052] Figure 6 This is the XRD pattern of the ZSM-5 molecular sieve prepared in Comparative Example 1.

[0053] Figure 7 The nitrogen adsorption-desorption curve and pore size distribution curve of the beta molecular sieve prepared in Comparative Example 2.

[0054] Figure 8 XRD pattern of the beta molecular sieve prepared in Comparative Example 2.

[0055] Fig. 9 The nitrogen adsorption-desorption curve and pore size distribution curve of the MOR molecular sieve prepared in Comparative Example 5 are shown.

[0056] Fig.10 XRD pattern of the MOR molecular sieve prepared in Comparative Example 5. DETAILED DESCRIPTION

[0057] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0058] The commercially available carbonized coconut shell used in the following experiments was produced by Huayu Zhengda, with an iodine value of 1000.

[0059] Preparation Example 1

[0060] This embodiment prepares a nearly spherical carbonized coconut shell, and the preparation method is as follows:

[0061] Commercially available carbonized coconut shell (also known as coconut shell charcoal) is screened with a sieve to obtain carbonized coconut shell with a particle size of 20-40 mesh; the carbonized coconut shell with a particle size of 20-40 mesh is transferred to a stainless steel ball mill for ball milling, and the friction and collision between the carbonized coconut shells are used during the ball milling process to remove the irregular edges and corners of the carbonized coconut shell particles to obtain ellipsoidal or spherical carbonized coconut shell particles; the ball-milled carbonized coconut shell is screened to obtain 30-40 mesh approximately spherical carbonized coconut shell particles, and then dried in a 60° C. blast oven for 12 hours; the dried nearly spherical carbonized coconut shell particles are placed in a room temperature dryer for standby use.

[0062] Preparation Example 2

[0063] This embodiment prepares a nearly spherical carbonized coconut shell, and the preparation method is as follows:

[0064] Commercially available carbonized coconut shell (also known as coconut shell charcoal) is screened with a sieve to obtain carbonized coconut shell with a particle size of 20-40 mesh; the carbonized coconut shell with a particle size of 20-40 mesh is transferred to a stainless steel ball mill for ball milling, and the friction and collision between the carbonized coconut shells are used during the ball milling process to remove the irregular edges and corners of the carbonized coconut shell particles to obtain ellipsoidal or spherical carbonized coconut shell particles; the ball-milled carbonized coconut shell is screened to obtain approximately spherical carbonized coconut shell particles with a particle size of 30-40 mesh, and then dried in a 60° C. blast oven for 12 hours;

[0065] The dried nearly spherical carbonized coconut shell particles are subjected to high-temperature nitrogen carbonization treatment, and the treatment conditions are flowing nitrogen at a constant temperature of 800°C for 4 hours; the high-temperature nitrogen carbonization treatment can remove the water molecules and small molecules adsorbed in the carbonized coconut shell, and at the same time, the uncarbonized tissue can be fully carbonized; the carbonized coconut shell obtained by the high-temperature nitrogen carbonization treatment is placed in a room temperature dryer for standby use.

[0066] Preparation Example 3

[0067] This embodiment prepares a nearly spherical porous SiO2 ball, and the preparation method is as follows:

[0068] Weigh 200.0g silica sol (SiO2 content 30wt%), add 25ml ammonia water (4+1, the volume ratio of concentrated ammonia water to water is 4:1) under stirring to obtain a white gel; after the addition of ammonia water (4+1) is completed, continue stirring for 20min, then stop stirring, and dry in a 120℃ forced air oven; during the drying process, water molecules and ammonia molecules will escape in the form of gas to form pores; after drying, break the irregular SiO2 blocks to obtain irregular SiO 2 blocks are screened to obtain SiO2 particles with a particle size of 20-40 mesh; the 20-40 mesh SiO2 particles are transferred to a stainless steel ball mill for ball milling. During the ball milling process, the friction and collision between the SiO2 particles are used to remove the irregular edges and corners of the SiO2 particles to obtain ellipsoidal or spherical SiO2 particles; the ball-milled SiO2 particles are then screened to obtain 30-40 mesh approximately spherical SiO2 particles, which are then dried in a 60°C blast oven for 12 hours. The dried approximately spherical SiO2 particles are placed in a room temperature dryer for later use.

[0069] Preparation Example 4

[0070] This embodiment prepares a nearly spherical hard carbon material, and the preparation method thereof is as follows:

[0071] Weigh 500.0g of lignite, place it in a 120℃ blast oven for baking and drying for 6 hours to remove moisture and volatile components; then place it in a high-temperature roasting furnace and carbonize it in a nitrogen environment at 1500℃ for 12 hours; after carbonization, crush it to obtain irregular hard carbon blocks, sieve the irregular hard carbon blocks to obtain hard carbon particles with a particle size of 20-40 mesh; transfer the 20-40 mesh hard carbon particles to a stainless steel ball mill for ball milling, and use the friction and collision between the hard carbon particles during the ball milling process to remove the irregular edges of the hard carbon particles to obtain ellipsoidal or spherical hard carbon particles; then sieve the ball-milled hard carbon particles to obtain 30-40 mesh approximately spherical hard carbon particles, and then dry them in a 60℃ blast oven for 12 hours. The dried hard carbon particles are placed in a room temperature dryer for standby use.

[0072] Example 1

[0073] This embodiment provides an acoustic capacity-enhancing material, such as Figure 1 As shown, the preparation method of the acoustic capacity increasing material comprises:

[0074] 1. Weigh 50.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 1.5 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;

[0075] 2. Weigh 1.313 g Al(NO3)3·9H2O as aluminum source, dissolve it in 23.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;

[0076] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 0.25 g of ZSM-5 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;

[0077] 4. Add 10.0 g of carbonized coconut shell prepared in Preparation Example 1 to the above molecular sieve mother liquor, continue stirring for 1 h to obtain a mixture, transfer the mixture to a PTFE-lined reactor, and crystallize at a constant temperature of 120° C. for 96 h; after the crystallization, the molecular sieve mother liquid crystalizes to form a ZSM-5 molecular sieve, and the crystallized product is centrifuged and washed several times, and dried at 100° C. overnight to obtain an acoustic volume-enhancing material product.

[0078] The ZSM-5 molecular sieve formed in this embodiment has two-dimensional interconnected pores. In this embodiment, the porous material (molecular sieve) in the acoustic capacity-enhancing material product (also known as: host material) accounts for 47.34%wt of the acoustic capacity-enhancing material product.

[0079] Example 2

[0080] This embodiment provides an acoustic capacity increasing material, and the preparation method of this embodiment is basically the same as the preparation method of Example 1, except that 10.0 g of the carbonized coconut shell of Preparation Example 2 is used in this embodiment instead of 10.0 g of the carbonized coconut shell of Preparation Example 1. In this embodiment, the porous material (molecular sieve) in the acoustic capacity increasing material product accounts for 47.31%wt of the acoustic capacity increasing material product.

[0081] Example 3

[0082] This embodiment provides an acoustic capacity-enhancing material, such as Figure 1 As shown, the preparation method of the acoustic capacity increasing material comprises:

[0083] 1. Mix 27.0 g of water and 0.938 g of Al(NO3)3·9H2O evenly, then add 1.555 g of NaOH and stir at room temperature for 0.5 h to obtain solution A;

[0084] 2. After solution A is clarified, add 50 g of silica sol (SiO2 content 30% wt) dropwise under vigorous stirring. The solution gradually turns into a milky white sol. Continue stirring until the sol becomes uniform to obtain solution B.

[0085] 3. Add 0.5 g of Beta molecular sieve as seed crystals to solution B. The amount of seed crystals added is calculated to be 10% of the mass of SiO2 input. Stir for 0.5 h to complete the preparation of molecular sieve mother solution.

[0086] 4. Add 10.0 g of the carbonized coconut shell of Preparation Example 1 to the above molecular sieve mother liquor, continue stirring for 1 hour to obtain a mixture; transfer the mixture to a PTFE-lined reactor and crystallize at a constant temperature of 160° C. for 36 hours; after the crystallization, the molecular sieve mother liquid crystalizes to form a beta molecular sieve, and the crystallized product is centrifuged and washed several times, and dried at 100° C. overnight to obtain an acoustic volume-enhancing material product.

[0087] The Beta molecular sieve formed in this embodiment has three-dimensional interconnected pores. In this embodiment, the porous material (molecular sieve) in the acoustic capacity-enhancing material product accounts for 46.37%wt of the acoustic capacity-enhancing material product.

[0088] Example 4

[0089] This embodiment provides an acoustic capacity increasing material, and the preparation method of this embodiment is basically the same as the preparation method of Example 3, except that: this embodiment uses 10.0g of carbonized coconut shell of Preparation Example 2 instead of 10.0g of carbonized coconut shell of Preparation Example 1. In this embodiment, the porous material (molecular sieve) in the acoustic capacity increasing material product accounts for 46.74%wt of the acoustic capacity increasing material product.

[0090] Example 5

[0091] This embodiment provides an acoustic capacity-enhancing material, such as Figure 1 As shown, the preparation method of the acoustic capacity increasing material comprises:

[0092] 1. Weigh 50.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 1.5 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;

[0093] 2. Weigh 1.313 g Al(NO3)3·9H2O as aluminum source, dissolve it in 23.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;

[0094] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 0.25 g of ZSM-5 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;

[0095] 4. Continue to add 10.0 g of the nearly spherical hard carbon material in Preparation Example 4 to the above molecular sieve mother liquor, continue stirring for 1 hour to obtain a mixture, transfer the mixture to a PTFE-lined reactor, and crystallize at a constant temperature of 120°C for 96 hours; after the crystallization is completed, the molecular sieve mother liquid crystalizes to form a ZSM-5 molecular sieve, and the crystallized product is centrifuged and washed several times, and dried at 100°C overnight to obtain an acoustic volume-enhancing material product.

[0096] The ZSM-5 molecular sieve formed in this embodiment has two-dimensional interconnected pores. In this embodiment, the porous material (molecular sieve) in the acoustic capacity-enhancing material product (also known as: host material) accounts for 47.24%wt of the acoustic capacity-enhancing material product.

[0097] Example 6

[0098] This embodiment provides an acoustic capacity-enhancing material, such as Figure 1 As shown, the preparation method of the acoustic capacity increasing material comprises:

[0099] 1. Weigh 50.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, add 1.5 g of NaOH as an alkali source and mineralizer, and stir rapidly at room temperature for 0.5 h, which is recorded as solution A;

[0100] 2. Weigh 1.313 g Al(NO3)3·9H2O as aluminum source, dissolve it in 23.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is recorded as solution B;

[0101] 3. Slowly add solution B to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 0.25 g of ZSM-5 molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;

[0102] 4. Continue to add 10.0 g of the porous SiO2 microspheres in Preparation Example 3 to the above molecular sieve mother liquor, continue stirring for 1 hour to obtain a mixture, transfer the mixture to a PTFE-lined reactor, and crystallize at a constant temperature of 120°C for 96 hours; after the crystallization is completed, the molecular sieve mother liquid crystalizes to form a ZSM-5 molecular sieve, the crystallized product is centrifuged and washed several times, and dried at 100°C overnight to obtain an acoustic volume-enhancing material product.

[0103] The ZSM-5 molecular sieve formed in this embodiment has two-dimensional interconnected pores. In this embodiment, the porous material (molecular sieve) in the acoustic capacity-enhancing material product (also known as: host material) accounts for 46.34%wt of the acoustic capacity-enhancing material product.

[0104] Comparative Example 1

[0105] This comparative example provides a method for preparing a ZSM-5 molecular sieve material by a seed crystal method. The material preparation process (including the reagents and amounts used, and crystallization conditions) is the same as steps 1 to 3 in Example 1, but without introducing carbonized coconut shell.

[0106] Comparative Example 2

[0107] This comparative example provides a method for preparing beta molecular sieve material by seed crystal method, and the material preparation process (including reagents and amounts used, crystallization conditions) is the same as steps 1 to 3 in Example 3, but without introducing carbonized coconut shell.

[0108] Comparative Example 3

[0109] This comparative example provides an acoustic volume-increasing material, and the preparation method of the acoustic volume-increasing material comprises:

[0110] 1. Weigh 50.0 g of silica sol (SiO2 content 30 wt%) as a silicon source, dissolve 1.875 g of NaOH as an alkali source in 25.0 g of deionized water to obtain a NaOH solution; add the NaOH solution dropwise to the silica sol under rapid stirring at room temperature, and continue stirring for 0.5 h after the addition is completed. This is recorded as solution A;

[0111] 2. Weigh 1.172 g Al(NO3)3·9H2O as the aluminum source, dissolve it in 15.0 g deionized water, and stir rapidly at room temperature for 0.5 h, which is referred to as solution B;

[0112] 3. Add solution B dropwise to solution A, and stir continuously at room temperature for 0.5 h to obtain a mixed solution; add 0.5 g of mordenite molecular sieve seed crystals to the mixed solution, and stir at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution;

[0113] 4. Add 10.0 g of carbonized coconut shell prepared in Preparation Example 1 to the above molecular sieve mother liquor, continue stirring for 1 h to obtain a mixture, transfer the mixture to a PTFE-lined reactor, and crystallize at a constant temperature of 160° C. for 48 h; after the crystallization, the molecular sieve mother liquid crystallizes to form a mordenite molecular sieve, and the crystallized product is centrifuged and washed several times, and dried at 100° C. overnight to obtain an acoustic volume-enhancing material product.

[0114] The mordenite MOR molecular sieve formed in this comparative example has pores in one-dimensional direction. In this comparative example, the porous material (molecular sieve) in the acoustic capacity-enhancing material product accounts for 45.89%wt of the acoustic capacity-enhancing material product.

[0115] Comparative Example 4

[0116] This comparative example provides an acoustic capacity increasing material, and the preparation method of this comparative example is basically the same as the preparation method of comparative example 3, except that: this comparative example uses 10.0g of carbonized coconut shell of preparation example 2 instead of 10.0g of carbonized coconut shell of preparation example 1. In this comparative example, the porous material (molecular sieve) in the acoustic capacity increasing material product accounts for 45.62%wt of the acoustic capacity increasing material product.

[0117] Comparative Example 5

[0118] This comparative example provides a method for preparing a mordenite molecular sieve material by a seed crystal method. The material preparation process (including the amount of reagents used and crystallization conditions) is the same as steps 1 to 3 in comparative example 3, but without introducing carbonized coconut shell.

[0119] The carbonized coconut shells in Preparation Example 1, Preparation Example 2, Examples 1 to 4, Comparative Example 3 and Comparative Example 4 all have mesopores and macropores, the mesopore diameter is 2nm-50nm, and the macropore diameter is 50nm-20μm.

[0120] Figure 2 The nitrogen adsorption-desorption curve and micropore size distribution curve of the ZSM-5 molecular sieve of Comparative Example 1 are shown in FIG. Figure 2 It can be seen that the ZSM-5 molecular sieve has a high specific surface area, which can reach 350m 2 / g or above, and the pore size is about 0.5nm.

[0121] Figure 3 This is a SEM photo of the carbonized coconut shell in Preparation Example 1. It can be seen that the carbonized coconut shell used in the present invention has a pore structure, including mesopores and macropores, the mesopore diameter is 2nm-50nm, and the macropore diameter can reach 50nm-20μm.

[0122] Figure 4 , Figure 5 This is a SEM photo of the acoustic capacity-enhancing material prepared in Example 2. From the low-magnification photo ( Figure 4 ) It can be seen that the morphology of the acoustic volume-enhancing material is porous spherical, and the high-magnification SEM photo ( Figure 5 ) It can be seen that the molecular sieve is loaded or embedded in the internal pores of the carbonized coconut shell.

[0123] Figure 6 This is the XRD diagram of the ZSM-5 molecular sieve prepared in Comparative Example 1. The "MFI" in the figure is the simulated XRD result of the IZA website MFI. It can be seen that the ZSM-5 molecular sieve has a typical MFI topological structure and a high crystallinity of more than 80%.

[0124] Figure 7 The nitrogen adsorption-desorption curve and micropore size distribution curve of the Beta molecular sieve prepared in Comparative Example 2 are shown in FIG. Figure 7 It can be seen that the molecular sieve has a high specific surface area, which can reach 370m 2 / g, and the pore size is about 0.6nm.

[0125] Figure 8This is the XRD diagram of the beta molecular sieve prepared in comparative example 2. The "BEA" in the figure is the simulated XRD result of the BEA topology of the IZA website. It can be seen that the beta molecular sieve has a typical BEA topology structure and a high crystallinity of more than 80%.

[0126] Fig. 9 The nitrogen adsorption-desorption curve and micropore size distribution curve of the mordenite molecular sieve of comparative example 5 are shown in FIG. Fig. 9 It can be seen that the specific surface area of ​​the molecular sieve reaches 300m 2 / g, and the pore size is about 0.6nm.

[0127] Fig.10 This is the XRD diagram of the MOR molecular sieve prepared in comparative example 5, where "MOR" is the simulated XRD result of the MOR topology of the IZA website. It can be seen that the MOR molecular sieve has a typical MOR topological structure and a high crystallinity of more than 80%.

[0128] Test Example 1

[0129] This test example provides the acoustic test results of the products prepared in Preparation Example 1 to Preparation Example 2, Example 1 to Example 6, and Comparative Example 1 to Comparative Example 5.

[0130] Before testing, the products of each experiment were filtered and sieved, and the products with a particle size of 20-40 mesh were used as the test samples. During the filtering operation, the molecular sieves that were not loaded in the coconut shell in the acoustic volume-enhancing material could be removed.

[0131] The samples to be tested are filled in a standard sound cavity for acoustic performance testing. The filling amount of each sample to be tested is 300 mg, the volume of the standard sound cavity is 1.0 cubic centimeter, and the structure of the standard sound cavity is the acoustic material test fixture assembly described in CN215072984U (invention name "An acoustic material test fixture assembly", application number 202120796674.2), and the full text of the patent is introduced here as a reference. The test signal is an analog program signal or pink noise signal specified in GB / T 12060.1 "Acoustic System Equipment Part 1: Overview". The test results are summarized in Table 1.

[0132] Table 1

[0133]

[0134] As can be seen from Table 1, compared with carbonized coconut shell and molecular sieve alone, the carbonized coconut shell loaded with molecular sieve particles as an acoustic volume-increasing material in the present invention has a better effect of improving low frequencies, indicating that carbonized coconut shell and molecular sieve can synergistically improve low-frequency effects.

[0135] Furthermore, compared with the acoustic volume-increasing material made from the carbonized coconut shell that has not been subjected to high-temperature treatment, the acoustic volume-increasing material prepared using the carbonized coconut shell that has been subjected to high-temperature treatment as a carrier has a better effect of improving low frequencies.

[0136] Compared with using mordenite having only one-dimensional pores as a porous material, using molecular sieves having two-dimensional pores and three-dimensional pores as porous materials can effectively improve the low-frequency effect.

[0137] It can be seen from the above results that the present invention can combine the advantages of light weight and large air adsorption capacity of the carrier material with the advantages of regular channels and pore structure of the porous material by loading the porous material with two-dimensional and three-dimensional channels into the porous carbon material, thereby systematically improving the acoustic low-frequency effect.

Claims

1. An acoustic volume-enhancing material, comprising a host carrier and a porous material, wherein the host carrier has a pore structure, and the pore structure includes mesopores and macropores; The porous material is loaded on and / or embedded in the pore structure of the host carrier; the porous material has two-dimensional pores and / or three-dimensional pores, and the pore size of the two-dimensional pores and / or three-dimensional pores in the porous material is The channels are interconnected.

2. The acoustic volume enhancement material according to claim 1, wherein: The pore size of the mesopores of the host carrier is 2nm-50nm, and the pore size of the macropores of the host carrier is 50nm-20μm.

3. The acoustic volume-enhancing material according to claim 1 or 2, wherein: The host carrier includes one or a combination of two or more of porous carbon material and porous silicon dioxide; Preferably, the porous carbon material comprises one or a combination of two or more of carbonized coconut shell, soft carbon, hard carbon, carbon molecular sieve, and functionalized activated carbon; Preferably, the host carrier can withstand temperatures above 200°C.

4. The acoustic capacity-enhancing material according to claim 1, wherein: The porous material includes an inorganic material having micropores and / or an organic framework material having micropores; Preferably, the inorganic material having micropores comprises a molecular sieve; Preferably, the organic framework material with micropores comprises one or a combination of two or more of a hyper-crosslinked polymer, a conjugated microporous polymer, a metal organic framework material, a porous aromatic framework, and a covalent triazine framework; More preferably, the crystallinity of the molecular sieve is above 80%; More preferably, the specific surface area of ​​the molecular sieve is 250 m 2 / g or more, more preferably 350m 2 / g or more; Preferably, the molecular sieve comprises one or a combination of two or more of phosphorus aluminum molecular sieve, pure silicon molecular sieve, silicon aluminum molecular sieve, and silicon phosphorus aluminum molecular sieve; Preferably, the molecular sieve comprises ZSM-5 molecular sieve and / or Beta molecular sieve.

5. The acoustic capacity-enhancing material according to claim 1, wherein: The mass ratio of the host carrier to the porous material is 4:1-1:4; Preferably, the mass ratio of the host carrier to the porous material is 2:1-1:

2.

6. A method for preparing the acoustic volume-enhancing material according to any one of claims 1 to 5, comprising: Immersing the host carrier in a solution of a porous material precursor and crystallizing it to obtain the acoustic volume-enhancing material; Wherein, the preparation method does not include a calcination step.

7. The preparation method according to claim 6, wherein: The parasite carrier is a pre-treated parasite carrier, and the pre-treatment process includes: treating the parasite carrier at a high temperature of 450° C.-800° C. in a protective atmosphere for more than 2 hours.

8. The preparation method according to claim 6, wherein: The porous material precursor solution includes a molecular sieve mother solution without a template; Preferably, the molecular sieve mother liquor contains seed crystals.

9. A speaker module, wherein: The speaker module comprises the acoustic volume-enhancing material according to any one of claims 1 to 5; Preferably, the acoustic volume-increasing material is filled inside the speaker module; Preferably, a speaker is provided in the resonance cavity of the speaker module, and the acoustic volume increasing material is filled in the resonance cavity of the speaker module.

10. An electronic device, comprising the speaker module according to claim 9; Preferably, the electronic device is a smart phone, a smart watch, a tablet computer, smart glasses, VR glasses, a smart speaker or a laptop computer; Preferably, the electronic device is provided with a sound output opening and a sound output channel, and the speaker module is acoustically coupled with the sound output opening through the sound output channel; More preferably, the speaker module is integrally formed with the electronic device; or, the electronic device further includes a casing, and the speaker module is disposed in an internal space formed by the casing.

Citation Information

Patent Citations

  • Acoustic material testing tool assembly

    CN215072984U

Cited By

  • Sound production device and electronic equipment

    CN120583355A